Resposta :
Explicação passo-a-passo:
A'
x² - 5x + 6 = 0
a= 1; b = -5; c = 6
D = -5² - 4 . 1 . 6
D = 25 - 24
D = 1
x' = (-(-5) + 1)/(2 . 1)
x' = (5 + 1)/(2)
x' = (6)/(2)
x' = 3
x" = (-(-5) - 1)/(2 . 1)
x" =( 5 - 1)/( 2)
x'' = (4)/( 2)
x'' = 2
Raízes: 2 e 3
B'
2x² - 3x + 1 = 0
a= 2; b = -3; c = 1
D = -3² - 4 . 2 . 1
D = 9 - 8
D = 1
x' = (-(-3) + 1)/(2 . 2)
x' = (3 + 1)/(4)
x' = (4)/(4)
x' = 1
x" = (-(-3) - 1)/(2 . 2)
x" =( 3 - 1)/( 4)
x'' = (2)/( 4)
x'' = 1/2
Raízes: 1/2 e 1
C'
y= (x+3) . (x-5)
Raízes 3 e 5, pois se
x+3=0
x = -3
e se:
x-5=0
x = 5